Management Model Development for The Techno-Entrepreneurship Learning Sustainability in Higher Education - Batmetan, Johan Reimon; Palilingan, Verry Ronny (Indonesian Journal of Business and Entrepreneurship, 2022)
Techno-entrepreneurship learning becomes an important field taught in universities. The sustainability of this learning was agreed upon on the management strategies applied and the approved content. This research aimed to examine management strategies applied in the continuous learning of techno-entrepreneurship in higher education. This research used qualitative methods to formulate management strategies to ensure the sustainability of learning techno-entrepreneurship in higher education. The results of this study indicate that appropriate management strategies significantly influence the sustainability of learning techno-entrepreneurship in higher education. This study concluded that with the right and ensuring management strategies, techno-entrepreneurial learning is an attractive choice to be studied in higher education.Keywords: higher education, innovation, learning sustainability, management model, techno-entrepreneurship